2019
DOI: 10.1038/s41598-019-54176-0
|View full text |Cite
|
Sign up to set email alerts
|

Physics-informed Deep Learning for Dual-Energy Computed Tomography Image Processing

Abstract: Dual-energy CT (DECT) was introduced to address the inability of conventional single-energy computed tomography (SECT) to distinguish materials with similar absorbances but different elemental compositions. However, material decomposition algorithms based purely on the physics of the underlying attenuation process have several limitations, leading to low signal-to-noise ratio (SNR) in the derived material-specific images. To overcome these, we trained a convolutional neural network (CNN) to develop a framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…For rods within the training mask (1-9), the CNN explicitly preserves the chain B contrast (maximum error by magnitude, 0.33 HU). For rods outside of the training mask and in the training halo (10)(11)(12)(13)(14)(15), however, the CNN spectral extrapolation results are less consistent, particularly for the 2 and 15 mg/mL iodine rods (contrast estimation errors: −17.34 and −28.89 HU, respectively). Compared with the much smaller average errors seen in the testing data (Fig.…”
Section: B Gammex Phantommentioning
confidence: 98%
See 1 more Smart Citation
“…For rods within the training mask (1-9), the CNN explicitly preserves the chain B contrast (maximum error by magnitude, 0.33 HU). For rods outside of the training mask and in the training halo (10)(11)(12)(13)(14)(15), however, the CNN spectral extrapolation results are less consistent, particularly for the 2 and 15 mg/mL iodine rods (contrast estimation errors: −17.34 and −28.89 HU, respectively). Compared with the much smaller average errors seen in the testing data (Fig.…”
Section: B Gammex Phantommentioning
confidence: 98%
“…This includes a growing body of work on CNN‐based postreconstruction denoising for reproducing full‐dose CT data from low‐dose CT data 9–11 . More relevant here, this also includes several papers demonstrating the advantages of spatial contextual information in the problems of material decomposition 12–14 and the synthesis of noncontrast images 15 and monochromatic images 16 . More broadly, application of deep learning to the problem of spectral extrapolation is motivated by prior successes in a number of closely related image processing problems, including inpainting, 17 pan‐sharpening, 18 and assigning color to grayscale images 19 …”
Section: Introductionmentioning
confidence: 99%
“…There has been increasing work in physics-informed AI/deep learning (e.g., [89]), and image reconstruction is no exception. The goal here is to combine the power of the AI paradigm with our existing knowledge of the imaging physics and statistical modeling, seeking a hybrid new image reconstruction methodology that exploits the best of AI with the best of our understanding of imaging physics and reconstruction.…”
Section: B Regularization By Deep-learned Analysismentioning
confidence: 99%
“…In some patients, particularly those with a large body habitus and those scanned with low-dose, the iterative reconstruction methods can have high noise and artifacts. A recent study reported that physics-informed and anatomic information-trained CNNbased DL could help reconstruct non-contrast single-energy CT from DECT scans with higher fidelity than the processed DECT image datasets [122]. At the time of writing this manuscript, AiCE has been FDA approved for commercial use.…”
Section: Emerging Technologies and Dl-based Reconstructionmentioning
confidence: 99%